Early detection in a mouse model of pancreatic cancer by imaging DNA damage response signalling - Cornelissen, B; Knight, J; Baguna Torres, J; Goldin, R; Mosley, M; Dias, G; Contreras Bravo, L; Kersemans, V; Allen, P; Mukherjee, S; Smart, S (Society of Nuclear Medicine, 2019)
Rationale: Despite its widespread use in oncology, the PET radiotracer 18F-FDG is ineffectivefor improving early detection of pancreatic ductal adenocarcinoma (PDAC). An alternative strategy for early detection of pancreatic cancer involves visualisation of high-grade pancreatic intraepithelial neoplasias (PanIN-3), generally regarded as the non-invasive precursors of PDAC. The DNA damage response is known to be hyper-activated in late-stage PanINs. Therefore, we investigated whether the SPECT imaging agent, 111In-anti-γH2AX-TAT, allows visualisation of the DNA damage repair marker γH2AX in PanIN-3s in an engineered mouse model of PDAC, to facilitate early detection of PDAC. Methods: Genetically engineered KPC mice (KRasLSL.G12D/+; p53LSL.R172H/+; PdxCre) were imaged with 18F-FDG and 111In-anti-γH2AX-TAT. PanIN/PDAC presence visualised by histology was compared with autoradiography and immunofluorescence. Separately, the survival of KPC mice imaged with 111In-anti-γH2AX-TAT was evaluated. Results: In KPC mouse pancreata, γH2AX expression was increased in high-grade PanINs, but not in PDAC, corroborating earlier results obtained from human pancreas sections. Uptake of 111In-anti-γH2AX-TAT, but not 111In-IgG-TAT or 18F-FDG, within the pancreas was positively correlated with the age of KPC mice, which was correlated with the number of highgrade PanINs. 111In-anti-γH2AX-TAT localises preferentially in high-grade PanIN lesions, but not in established PDAC. Younger, non-tumour-bearing KPC mice that show uptake of 111Inanti-γH2AX-TAT in the pancreas survive significantly shorter than mice with physiological 111In-anti-γH2AX-TAT uptake. Conclusion: 111In-anti-γH2AX-TAT imaging allows non-invasive detection of DNA damage repair signalling upregulation in pre-invasive PanIN lesions and is a promising new tool to aid in the early detection and staging of pancreatic cancer.